Transforming Inclusive Digital Pedagogy in Malaysian Tertiary TVET: Adapting to a New Educational Landscape - Mohd Ridhuan Mohd Jamil; Nadzimah Idris; Mohd Muslim Md Zalli; Nik Muhammad Hanis Nek Rakami; Zetra Hainul Putra (Journal of Technical Education and Training, 2024)
The COVID-19 pandemic has greatly sped up the use of Artificial Intelligence (AI) and Information and Communication Technology (ICT) in education. The aim is to create a more inclusive and fair system, especially in Technical and Vocational Education and Training (TVET) for individuals with special needs. This approach focuses on personalized learning, high-quality information, and employer involvement, even though it is challenging to replicate traditional classroom experiences. Using the fuzzy Delphi technique, the methodology adapts inclusive digital teaching to changing needs, stressing infrastructure, accessibility, personalized learning, digital skills development, and teacher capabilities. Malaysia is working to become a global leader in education by using ICT to support student-centered learning and develop digital skills, in line with the National Digital Policy. The results show a strong potential for building a thorough digital education system. This integration has important effects on improving educational infrastructure, accessibility, and teacher skills, helping Malaysia establish itself as a leader in the global education scene.